PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL DAN KOMUNIKASI TERHADAP KOMITMEN ORGANISASI DENGAN BUDAYA ORGANISASI SEBAGAI VARIABEL INTERVENING PADA DINAS PEKERJAAN UMUM DAN PENATAAN RUANG KABUPATEN NIAS - Arsyam Mendrofa; Jonner Lumban Gaol; Sarman Sinaga (JURNAL PROINTEGRITA, 2022)
Several factors influencing organizational commitment are transformational leadership, communication, and factors that indirectly affect organizational commitment are organizational culture. This study aims at determining the effect of transformational leadership style and organizational communication on organizational commitment with organizational culture as an Intervening Variable at the Office of Public Works and Spatial Planning in Nias Regency. The sample in this study amounted to 74 respondents. By using simple random sampling method. This type of research is quantitative research with path analysis techniques and using questionnaire data. In the path analysis hypothesis test, namely with multiple linear analysis, classical assumptions and intervening tests. Based on the results of the research by testing the hypothesis that the transformational leadership style variable partially has no significant effect on organizational culture, while the organizational communication variable partially has a significant effect on organizational culture. The variables of transformational leadership style and organizational communication have a simultaneous effect on organizational culture. The variables of transformational leadership style and organizational communication have a simultaneous effect on organizational commitment. The variables of transformational leadership style and organizational communication partially have a significant effect on organizational commitment. The variables of transformational leadership style and organizational communication simultaneously affect organizational culture. Then the transformational leadership style on organizational commitment with organizational culture as an intervening variable has a positive and indirect effect. And finally, there is the influence of organizational communication on organizational commitment with organizational culture as an intervening variable.